PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, OPERATING CAPACITY, DAN FIRM SIZE TERHADAP FINANCIAL DISTRESS (Studi pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Syalam, Hamidah; Savitri, Enni; Putra, Adhitya Agri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this research is to test the influence of liquidity, leverage,profitability, operating capacity and firm size to financial distress on manufacturingcompenies listed on bursa efek Indonesia in the period of year 2014-2017.Data analysistechniques in this study using descriptive methods, sampling technique used withpurposive sampling method so that the research samples obtained as much as 12financial distress companies with the amount data observed as many as 48 observations.The result of hypothesis testing that liquidity proxied with current ratio has effect onfinancial distress. Leverage proxied with debt to equity ratio has no effect on financialdistress. Profitability proxied with return on asset has effect on financial distrees.Operating capacity proxied with total asset turnover has effect on financial distress. firmsize proxied with ln total asset has effect on financial distrees.Keyword : Liquidity, Leverage, Profitability, Operating Capacity, Firm Size, FinancialDistres